1985
DOI: 10.1073/pnas.82.20.6960
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific chloroplast recombination in a Nicotiana somatic hybrid

Abstract: Genetic recombination between chloroplasts of two flowering plant species, Nwotiana tabacum and Nicotana plumbaginifolia, after somatic cell fusion is described. The parental lines differed in three cytoplasmic genetic markers. The N. tabacum mutant SR1-A15 was streptomycin-resistant, defective in chloroplast greening, and lincomycin-sensitive. The N. plumbaginifolia mutant LR400 was streptomycinsensitive, normal green, and lincomycin-resistant. Streptomycin-resistant clones in cell culture are identified by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 235 publications
(72 citation statements)
references
References 21 publications
4
68
0
Order By: Relevance
“…These results have also demonstrated that in higher plants the high number of plastid DNA (ptDNA) copies in a plastid, and plastids in a cell, does not hamper the production of a stable and uniform plastome population of new genetic composition, provided segregation is directed by a suitably stringent selection pressure. Chloroplast gene transfer by recombination, however, seems to be accompanied by numerous, random recombination events scattered along the entire plastome (Fejes et a/., 1990;Medgyesy et al, 1985a). In experiments aimed at introducing defined changes, the use of cloned DNA sequences, and a transformation approach, is therefore, unavoidable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results have also demonstrated that in higher plants the high number of plastid DNA (ptDNA) copies in a plastid, and plastids in a cell, does not hamper the production of a stable and uniform plastome population of new genetic composition, provided segregation is directed by a suitably stringent selection pressure. Chloroplast gene transfer by recombination, however, seems to be accompanied by numerous, random recombination events scattered along the entire plastome (Fejes et a/., 1990;Medgyesy et al, 1985a). In experiments aimed at introducing defined changes, the use of cloned DNA sequences, and a transformation approach, is therefore, unavoidable.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic transformation gives the most useful results when the wild-type information can be stably exchanged with the desired new DNA sequences via homologous recombination. Although plastid DNA recombination is a frequent phenomenon in the green alga Chlamydomonas (Lemieux etal., 1981), higher plants with stably exchanged plastid genes have only been produced through stringent cell selection for genetic complementation after protoplast fusion (Medgyesy et a/., 1985a). In distant species combinations, where the entire plastome is non-functional with an alien nucleus, a limited plastid gene transfer by recombination has been able to overcome this incompatibility, offering a genetic tool to identify genes crucial in plastid-nucleus co-operation (Thanh and Medgyesy, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Absence of recombination between the plastid genomes suggested movement of intact organelles rather than naked, fragmented DNA (11,12). Indeed, chloroplasts rarely fuse (22), precluding recombination that enables new combinations of chloroplast genes.…”
Section: Discussionmentioning
confidence: 99%